PELAKSANAAN PEMBELAJARAN TEMATIK SD XAVERIUS DI BAWAH NAUNGAN YAYASAN XAVERIUS PALEMBANG - Utami, Tresiana Sari Diah (SCHOLASTICA JOURNAL : JURNAL PENDIDIKAN SEKOLAH DASAR DAN PENDIDIKAN DASAR (Kajian Teori dan Hasil Penelitian), 2018)
ABSTRACTThematic learning is essentially combining several subjects in one activity. The concept of thematic learning is the result of thoughts and studies of various educational theories. This research was conducted to determine the implementation of thematic learning in elementary schools under the auspices of the Palembang Xaverius Foundation. This research is part of the research on the development of listening learning materials. Data collection was carried out using the interview method and carried out in the odd semester of the 2016/2017 school year. The results showed that the school studied carried out thematic learning activities that were not in accordance with the concept of thematic learning.Keywords: learning, thematic, elementary school